FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA KELAS IX SMP UNTUK MELANJUTKAN KE SMKN 2 SIMPANG EMPAT KOMPETENSI KEAHLIAN PERAWAT KESEHATAN KABUPATEN TANAH BUMBU - Siti Nurmala (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThis research aims at revealing: 1) the students’ interst in continuing their study in health nursing expertisecompetency among IX Grade of Junior High School; 2) the direct effect of work opportunity knowledge, familyculture, self-understanding, and students’ economic background towards their interest in continuing their studyin health nursing expertise competency; 3) the indirect effects of work opportunity knowledge and the students’economic background toward their interest in continuing their study in health nursing expertise competency. Thepopulation of this research was IX Grade students of Junior High School who were officially registered in the secondsemester in the academic year of 2011/2012. The sample of the research was 248 students with proportional randomsampling technique. The research data were collected by using questionnaires. The results of this research showedthat (1) The students’ interest of IX Grade Junior High School to continue their study in health nursing expertisecompetency can be catagorized as high with average score of 59.02; (2) there were positive and significant directeffects of work opportunity knowledge, family culture, self-understanding, and economic background of the studentstoward their interest in continuing the study in health nursing expertise competency. (3) there were indirect effectsof work opportunity knowledge and economic background among IX Grade students of Junior High School towardtheir interest in continuing their study in health nursing expertise competency.Keywords: continuing study, health nursing, students interest.